Head and neck squamous cell carcinoma in young patients: a 26-year clinicopathologic retrospective study in a Brazilian specialized center - Tomo, Saygo [UNESP]; Neto, Sebastiao Conrado [UNESP]; Collado, Francisco Urbano [UNESP]; Mazza Sundefeld, Maria Lucia Marcal [UNESP]; Bernabe, Daniel Calera [UNESP]; Biasoli, Eder Ricardo [UNESP]; Miyahara, Glauco Issamu [UNESP] (Medicina Oral S L, 2020)
Background: To describe the clinicopathologic profile of young patients with head and neck squamous cell carcinoma (HNSCC) and compare to middle-aged and elderly adults. Material and Methods: Patients' individual records were reviewed for clinicopathologic data. Eighty-nine patients with age 18-45 years old met the inclusion criteria of the study. Two additional groups of middle-aged (n=89) and old (n=89) adults were set to comparative analysis. Results: Young patients represented 11.9% of all patients diagnosed with HNSCC. Women were more affected by HNSCC in the young and elder groups (p=0.04), and young patients were more prone to be non-smokers (p=0.01) and have lymph node metastasis at the time of diagnosis (p=0.04). In the young group, patients diagnosed with the disease in advanced stages were more prone to have a positive familial history of cancer (p=0.04), a positive status of alcohol consumption (p=0.03), and to be heavy drinkers (p=0.01). Survival was not different for the young group in comparison to the other groups. Conclusions: HNSCC in young patients had a different profile when compared to older patients, especially regarding sex and exposure to the classic risk factors for this disease. The survival of the young group is similar to the older groups and advanced clinical stage is predictor of worse survival.
Keywords: Mouth neoplasms; young adult; epidemiology